The proper use of residues from the sugar and ethanol agroindustry for the development of by-products: a review (Research, Society and Development, 2022)
The area responsible for the production of sugar, ethanol and sugarcane derivatives is the sugar and ethanol agroindustry, which stands out nationally for its production and technology used. The use of industrial waste, turning them into by-products, is responsible for the increase in gains, as the products previously considered problems, today become considerable sources of income for companies. The residues generated in the processing of sugarcane are: bagasse, filter cake, molasses or final honey and vinasse. The objective of the present work is to show that the residues generated in the course of industrial processes of sugar and alcohol production have great chances of becoming by-products, which serve for the development of new products and often return to the process in the production of energy. The creation of by-products from the waste generated in the processes, makes the industry make profits and throw less waste into the environment.